Estimation of the moment of inertia of a unit in a thermal power plant - Mijajlović, Anita; Dragosavac, Jasna; Klasnić, Ilija; Đorđević, Milan; Damjanac, Igor; Brdarević, Miloš (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
Increasing integration of renewable energy sources and the withdrawal of fossil-fuel generators reduce overall power-system inertia, making the grid more vulnerable to disturbances and threatening transient and frequency stability. Low inertia can lead to large frequency deviations, equipment damage, and financial losses, which highlights the need for accurate assessment of inertia contributions from remaining generation units and determination of the minimum inertia required for stable operation. While synchronous generator inertia constants are usually provided by manufacturers, corresponding data for steam turbines are often unavailable. Since post-fault transient stability depends on the true inertia of the combined generator–turbine assembly, this gap complicates stability studies. This paper proposes a method for estimating the inertia of turbogenerators using coast-down measurements from thermal unit B1 of the "Nikola Tesla B" power plant. The method is based on Newton’s rotational motion equation and enables more accurate evaluation of inertia in large thermal units.